Microwave-based vegetation descriptors in the parameterization of water cloud model at L-band for soil moisture retrieval over croplands - Zhen Wang; Tianjie Zhao; Jianxiu Qiu; Xuesheng Zhao; Rui Li; Shu Wang (GIScience & Remote Sensing, 2021)
Synthetic aperture radar (SAR) data have significant potential for soil moisture monitoring because of their high spatial resolution and independence from cloud coverage. However, it is challenging to retrieve soil moisture from SAR data over vegetated areas, as vegetation significantly affects backscattered radar signals. Auxiliary vegetation information obtained from optical images, such as the normalized difference vegetation index (NDVI) and the leaf area index (LAI), is commonly used to correct vegetation effects. However, it is generally difficult to obtain SAR and optical data in the same area simultaneously, because of the discrepancies in satellite coverage and the effects of cloud coverage. This study focuses on whether vegetation descriptors obtained directly from radar data at L-band can adequately parameterize the semi-empirical backscattering water cloud model (WCM) to support soil moisture retrieval. Four vegetation descriptors (three based on radar images and one based on optical images), were chosen to assess the parameterization and calibration of the WCM and the retrieval accuracy of soil moisture. The results showed that the vegetation descriptor of backscattering at VH polarization outperformed the other three vegetation descriptors (NDVI-derived vegetation water content, radar vegetation index, and the ratio of cross-polarization to VV polarization) in the investigation of four crop types (canola, corn, bean, and wheat) based on the Soil Moisture Active Passive Validation Experiment in 2012 (SMAPVEX12) in Canada. For the vegetation descriptor of VH, the overall accuracy of retrieved soil moisture was promising by separating into two growth stages, with unbiased root mean squared errors of 0.056, 0.053, 0.098, and 0.079 cm3/cm3 for canola, corn, bean, and wheat, respectively. The results also confirmed that variations in vegetation growth affect the accuracy of soil moisture retrieval. In addition, the retrieval performance was undermined when the vegetation changed dramatically, leading to variations or uncertainty in the vegetation structure. This study provides new insights into soil moisture retrieval methods with active L-band microwave observations.